2020
DOI: 10.1108/dlo-11-2019-0263
|View full text |Cite
|
Sign up to set email alerts
|

Techniques that facilitate knowledge hiding: perspectives of ethical dilemmas from both sides of the coin

Abstract: Purpose This paper examines the ethical dilemmas of a multi-dimensional contributor and end-user in the world of knowledge management by underscoring the different techniques of knowledge hiding observed in practice. Design/methodology/approach We categorize the ethical issues into identity, ownership, privacy, and reputation. We also analyze the different knowledge hiding techniques organizations can use to provide privacy to their contributors. Findings To help organizations better understand how to impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Existing studies on knowledge hiding agree regarding the intentional nature of knowledge hiding, and at present, scholars also understand that knowledge hiding can detrimentally affect organisations (Oliveira et al , 2021; Škerlavaj et al , 2018). Studies have identified various strategies, such as evasive hiding, playing dumb, rationalised hiding (Connelly et al , 2012), counter questioning (Kumar Jha and Varkkey, 2018), blatant lying and backstabbing (Issac et al , 2021), which typically comprise individuals’ knowledge hiding behaviour within organisations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies on knowledge hiding agree regarding the intentional nature of knowledge hiding, and at present, scholars also understand that knowledge hiding can detrimentally affect organisations (Oliveira et al , 2021; Škerlavaj et al , 2018). Studies have identified various strategies, such as evasive hiding, playing dumb, rationalised hiding (Connelly et al , 2012), counter questioning (Kumar Jha and Varkkey, 2018), blatant lying and backstabbing (Issac et al , 2021), which typically comprise individuals’ knowledge hiding behaviour within organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from conceptualising the construct, Connelly et al (2012) established the dimensionality of knowledge hiding. Studies have also established that knowledge hiding phenomenon is manifested variedly in different cultural contexts (Demirkasimoglu, 2015; Issac and Baral, 2021). Knowledge hiding even varies according to an individual’s experience within the organisation and the nature of the job (Issac et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness can toggle between different states of mind and consequently make the mind capable of obtaining a broader perspective on the subject at hand by clearly considering all circumstantial details through focused attention and clear awareness (Siegel et al, 2009). Therefore, mindfulness establishes a platform for sustainable knowledge creation, and the lack of prejudice and preconceived notions reinforces the potential for employees to be as productive as possible (Davenport and Prusak, 1998;Issac and Baral, 2021).…”
Section: Introductionmentioning
confidence: 99%